Unconventional modes in lasers with spatially varying gain and loss - Rotter, S. (2013)
We discuss a class of lasing modes created by a spatially inhomogeneous gain profile. These lasing modes are “extra modes,” in addition to, and very different from, conventional lasing modes, which arise from the passive cavity resonances. These new modes do not have high intensity across the entire gain region, but instead are localized at the gain boundary and throughout the gain-free region. They are surface modes, originating from the transmission resonances of the gain-free region. Using an S -matrix description we connect these surface modes to the lasing modes in PT -symmetric (balanced gain-loss) cavities.